Effective Approach to the Study of Aging: Grounded Theory Study - Amir Azizi; Mohamad Ali Sepahvandi; Negin Peyda; Javad Mohamadi (University of Social Welfare & Rehabilitation Sciences, 2016)
Objectives: Given the vulnerability of a lot of old people due to various physical, psychological, social, and family problems, we aimed to develop a theory in the field of aging based on systematic data collection. Methods & Materials: The current study is a type of qualitative research tradition method called information Grounded theory. The study sample consisted of 20 old age adults (10 women, 10 men), who were selected through purposive sampling. The statistical population comprised all old people in public places such as community parks, entertainment venues, offices, waiting rooms, and hospitals. After semi-structured interviews with 20 old people in the city of Tabriz and reviewing their opinions about their family members, a set of initial themes were collected and then some categories were extracted from them. Afterwards, during the core coding stage, the connection between these categories were determined in the frame of a paradigm with the following topics: causal conditions, phenomenon oriented, strategic issues, environmental conditions, intermediate category, and outcome categories. Next, in the stage of selective coding, the components of coding paradigm were described, the aging process was drawn and a theory awas developed. Results: Base on the study results, 6 main components and 39 subcomponents were extracted for aging and were presented in a theoretical model based on Grounded theory. Conclusion: Our findings, besides pointing to the mental health needs and emotional/family issues of the elderly, have emphasized the identification and conceptualizing of the different variables affecting old people lives based on Grounded theory.